Critical magnetic and magnetocaloric behavior of amorphous melt-extracted Gd50(Co69.25Fe4.25Si13B13.5)50 microwires. (July 2019) - Duc, N.T.M.; Shen, H.X.; Clements, E.; Thiabgoh, O.; Llamazares, J.L. Sanchez; Sanchez-Valdes, C.F.; Huong, N.T.; Sun, J.F.; Srikanth, H.; Phan, M.H.
Abstract: We report on the structural, magnetic, and magnetocaloric properties and critical behavior of high-quality amorphous melt-extracted Gd50 (Co69.25 Fe4.25 Si13 B13.5 )50 alloy microwires with an average diameter of 42 μm. The microwires undergo a second-order paramagnetic to ferromagnetic (PM-FM) transition around the Curie temperature, T C  ∼ 174 K. Around the PM-FM phase transition temperature, the magnetic entropy change Δ S M reaches a maximum value Δ S M max of about 5.9 J/kg K for a magnetic field change of 5 T. An iterative Kouvel-Fisher method was used to analyze the critical behavior of the second-order phase transition. The critical exponent values are β  = 0.493 ± 0.005, γ  = 1.321 ± 0.011, and δ  = 3.678 ± 0.073, which are close to those expected for the mean-field model with long-range interactions below T C and for the 3D-Heisenberg model with short-range interactions above T C . The magnetic and magnetocaloric behaviors of the Gd alloy microwires near the PM-FM phase transition are discussed. Highlights: High-quality amorphous melt-extracted Gd50 (Co69.25 Fe4.25 Si13 B13.5 )50 microwires. Large magnetocaloric effect and refrigerant capacity. Critical magnetic behavior and complex interactions. Magnetic refrigerator for nitrogen liquefaction.